2005
DOI: 10.1094/ats-2005-0728-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Zoysiagrass Varieties from Divot Injury

Abstract: Although zoysiagrasses (Zoysia japonica Steud., Z. matrella (L.) Merr, and Z. tenuifolia Willd.) provide an excellent golf course fairway or tee surface, their use in areas of intense play may be limited because of their relatively slow recuperative potential. The objective of the following research was to identify zoysiagrass varieties with improved recuperative potential that may be adapted to such situations. Divot injury was simulated in 2003 and 2004 on 24 zoysiagrass varieties maintained under golf cours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 4 publications
8
20
0
Order By: Relevance
“…Due to limited work on clipping yield of bermudagrass and zoysiagrass, it is difficult to compare clipping yield results in this study with previous research. The clipping yield rankings of zoysiagrass cultivars were similar to previous rankings on the establishment rate, stolon growth rate, and divot recovery of zoysiagrasses (20,32), where Palisades, El Toro, and Zenith had faster growth than Meyer. Although there were differences among bermudagrass cultivars across collection dates for clipping yield, they generally all had similar clipping yields.…”
Section: Clipping Yield Differences Among Cultivars and Speciessupporting
confidence: 77%
“…Due to limited work on clipping yield of bermudagrass and zoysiagrass, it is difficult to compare clipping yield results in this study with previous research. The clipping yield rankings of zoysiagrass cultivars were similar to previous rankings on the establishment rate, stolon growth rate, and divot recovery of zoysiagrasses (20,32), where Palisades, El Toro, and Zenith had faster growth than Meyer. Although there were differences among bermudagrass cultivars across collection dates for clipping yield, they generally all had similar clipping yields.…”
Section: Clipping Yield Differences Among Cultivars and Speciessupporting
confidence: 77%
“…Because research has not been conducted to compare divot recovery of bermudagrass and zoysiagrass in the same experiment, discussion comparing our findings with previous work is limited to tests evaluating single species. Similar to these findings, Karcher et al (4,5) observed cultivar performance differences across collection dates in divot recovery for bermudagrass and zoysiagrass. For divot recovery of bermudagrass in 2003, Karcher et al (4) found that Princess 77, Patriot, and Riviera had faster divot recoveries than Tifsport and Tifway, which is similar to findings of this study on 29 June 2009.…”
Section: Differences Exist In Divot Recovery Among Bermudagrass and Zsupporting
confidence: 61%
“…When comparing the findings of this research with Karcher et al (5), some similarities and differences existed in zoysiagrass divot recovery. Findings presented in this research support the relative fast recovery of Palisades and Zorro; however, Cavalier and Zenith had relatively slower recovery times compared to other cultivars in our experiment than reported in Karcher et al (5).…”
Section: Differences Exist In Divot Recovery Among Bermudagrass and Zsupporting
confidence: 54%
See 2 more Smart Citations